Analysis of the properties and microstructure of ultra-thin tube. Issue 1 (1st December 2022) - Yan, J P; Zhao, R; Meng, B; Wan, M; Wang, Z X
Abstract : In order to satisfy the requirement of the engine heat exchangers, ultra-thin tubes with higher dimensional accuracy and better performance are required. Inconel 718, as the basic material of ultra-thin tube, is one of the materials that can meet the requirements of the engine heat exchanger. In this study, ultra-thin tubes with diameters and thicknesses of 1.50mm and 0.050mm were prepared by floating plug drawing process. The results showed that the yield strength increased and the corresponding elongation decreased with the increase of drawing passes. The wall thickness of the ultra-thin tube can be controlled by floating plug drawing. And the inner surface quality was greatly improved compared with the initial tube. The inner surface roughness can be controlled below 1.7μm. The average grain size after drawing can be reduced from 4.9μm to 2.1μm.